2013
DOI: 10.1109/ted.2013.2262049
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Study of the Lattice Thermal Conductivity of Rough Graphene Nanoribbons

Abstract: Following our recent study on the electronic properties of rough nanoribbons [1], in this paper the role of geometrical and roughness parameters on the thermal properties of armchair graphene nanoribbons is studied. Employing a fourth nearest-neighbor force constant model in conjuction with the nonequilibrium Green's function method the effect of lineedge-roughness on the lattice thermal conductivity of rough nanoribbons is investigated. The results show that a reduction of about three orders of magnitude of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
(59 reference statements)
0
29
0
Order By: Relevance
“…The method is described in detail in our previous work, where we explored the length-dependence of the thermal conductance of GNRs [25,30]. We show that the exponent  is in fact not a single well-defined number, but it takes different values depending on whether the phonon transport is quasi-ballistic ( 1 The 4 th nearest-neighbor force-constant-method that we use (with parameters from [30]) can correctly regenerate the bandstructure of graphene as compared to experimental data [12], and also provides very good agreement with experimental data for rough GNRs with widths up to ~15 nm W [31]. Figure 1a shows for reference a typical phonon spectrum for a GNR channel of width 4 We extract the frequency dependent phonon transmission, ph T , and normalize it by the channel width W .…”
mentioning
confidence: 68%
“…The method is described in detail in our previous work, where we explored the length-dependence of the thermal conductance of GNRs [25,30]. We show that the exponent  is in fact not a single well-defined number, but it takes different values depending on whether the phonon transport is quasi-ballistic ( 1 The 4 th nearest-neighbor force-constant-method that we use (with parameters from [30]) can correctly regenerate the bandstructure of graphene as compared to experimental data [12], and also provides very good agreement with experimental data for rough GNRs with widths up to ~15 nm W [31]. Figure 1a shows for reference a typical phonon spectrum for a GNR channel of width 4 We extract the frequency dependent phonon transmission, ph T , and normalize it by the channel width W .…”
mentioning
confidence: 68%
“…Moreover, graphene is a zero-gap material and not suitable to use as thermoelectric material because of its very small Seebeck coefficient. However, theoretical studies revealed that phonon transport is sensitive to defects, strain, sample size and geometry [21] and it is known that by patterning graphene to form nanoribbons or anti-dots one can suppress the phonon contribution to heat transport [3]. This suppression is supported by experimental data, as reviewed in [2].…”
Section: Thermal Properties Of Graphenementioning
confidence: 88%
“…On the one hand efficient thermoelectricity requires a strongly suppressed thermal conductivity (κ) since the performance of thermoelectric devices is inversely proportional to the thermal conductivity. On the other hand, the cooling of local hot spots requires a high thermal conductivity [3]. Thermal conductance in a solid is defined by Fourier's law, where q is the heat flux, κ = κ pl + κ e is the thermal conductance due to phonons (κ pl ) and electrons (κ e ) and is the temperature gradient [1].…”
Section: Introductionmentioning
confidence: 99%
“…The transmission is significant in the entire energy spectrum and thus the whole spectrum contributes to thermal conductance for both the wide and narrow GNRs [26].…”
Section: B) Effect Of Roughness On Phonon Transmissionmentioning
confidence: 99%